2016
DOI: 10.1002/bmc.3817
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profile and pharmacokinetics of polyphyllin I, an anticancer candidate, in rats by UPLC‐QTOF‐MS/MS and LC‐TQ‐MS/MS

Abstract: Polyphyllin I (PPI), a natural steroidal saponin originating from rihzome of Paris polyphylla, is a potential anticancer candidate. Previous pharmacokinetics study showed that the oral bioavailability of PPI was very low, which suggested that certain amount of PPI might be metabolized in vivo. However, to date, information regarding the final metabolic fates of PPI is very limited. In this study, metabolites of PPI and their pharmacokinetics in rats were investigated using UPLC-QTOF-MS/MS and LC-TQ-MS/MS. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…The plasma concentration of an orally administered DG reached C max (132:5 ± 48:2 ng/mL) at 5:01 ± 0:55 h with an AUC of 4121:9 ± 1354:7 ng • h/mL and an absolute oral bioavailability of 4:45 ± 1:46% [32,33]. Similarly, Liu et al have demonstrated that treatment with DG resulted in a C max of 42:1 ± 30:4 ng/mL at 11:3 ± 3:9 h along with an AUC 0-60 h of 1309:3 ± 849:8 ng h/mL and t 1/2 of 10:4 ± 4:2 h [48]. It was suggested that a single dosage of DG administered to rats, monkeys, and dogs was mostly excreted into feces, while the amount absorbed was rapidly eliminated via bile.…”
Section: Bioavailability and Pharmacokinetic Studies Of Diosgeninmentioning
confidence: 88%
“…The plasma concentration of an orally administered DG reached C max (132:5 ± 48:2 ng/mL) at 5:01 ± 0:55 h with an AUC of 4121:9 ± 1354:7 ng • h/mL and an absolute oral bioavailability of 4:45 ± 1:46% [32,33]. Similarly, Liu et al have demonstrated that treatment with DG resulted in a C max of 42:1 ± 30:4 ng/mL at 11:3 ± 3:9 h along with an AUC 0-60 h of 1309:3 ± 849:8 ng h/mL and t 1/2 of 10:4 ± 4:2 h [48]. It was suggested that a single dosage of DG administered to rats, monkeys, and dogs was mostly excreted into feces, while the amount absorbed was rapidly eliminated via bile.…”
Section: Bioavailability and Pharmacokinetic Studies Of Diosgeninmentioning
confidence: 88%
“…Metabolomic analysis can detect changes in metabolism under different stimuli by analyzing the changes in endogenous small molecule metabolites ( 23 ). A previous study applied ultra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-QTOF/MS) for serum metabolomics and showed that the levels of amino acids and BAs are closely related to the occurrence and development of hyperlipidaemia ( 24 , 25 ). However, there have been no reports on the mechanism of action of LPLJ supplementation in liver metabolomics based on UHPLC-QTOF/MS in patients with hyperlipidaemia.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, several analytical methods using LC–MS/MS for quantification of steroidal saponins in complicated biological samples have been published so far (Wu, Zhang, Xu, et al, ; Wu, Zhang, Zhang, Xu, & Wang, ; Liu, Zhu, Shakya, & Wu, ; Yang et al, ), yet these methods either have low sensitivity or require a longer analysis time for sample analysis. In addition, in a previous study of method development for quantification of steroidal saponins (Yin, Qu, Zhang, et al, ; Yin, Qu, Li, et al, ), the sample preparation was time consuming.…”
Section: Introductionmentioning
confidence: 99%